Kandungan Betakaroten Kultur Mikroalga (Chlorella vulgaris) dengan Perbedaan Sumber Cahaya dan Kepadatan Awal Inokulum (KAI) - Teni Novianti (Universitas Wiralodra, 2019)
Chlorella vulgaris is one type of unicellular green microalgae with a cell diameter ranging from 2-8 microns. Pigments in Chlorella vulgaris besides functioning as antioxidant activity but also have a protective effect on retinal degeneration and strengthen the immune system. The purpose of this study was to determine the beta-carotene content of Microalgae Chlorella vulgaris cultured by treatment of light sources and different initial densities of inoculum. The method used was an experimental method, while the design of the study was a complete randomized factorial design consisted of 6 treatments and 3 repetitions. The treatments were light sources neon (32 watt) with an additional red LED, green LED and blue LED each for 16 watt with the Chlorella vulgaris inoculum initial density that was cultivated were 10x104 and 100x104 cells/ml. The result showed that the highest β-carotene content was 721,572 mg/l in the blue LED with inoculum initial density of 100x104 cells/ml.